2007
DOI: 10.1073/pnas.0611692104
|View full text |Cite
|
Sign up to set email alerts
|

Orai proteins interact with TRPC channels and confer responsiveness to store depletion

Abstract: The TRPC (C-type transient receptor potential) class of ion channels has been hypothesized to participate in store-operated Ca 2؉ entry (SOCE). Recently, however, STIM1 and Orai1 proteins have been proposed to form SOCE channels. Whether TRPCs participate in SOCE that is dependent on or regulated by Orai has not been explored. Here we show that Orai1 physically interacts with the N and C termini of TRPC3 and TRPC6, and that in cells overexpressing either TRPC3 or TRPC6 in a store-depletion insensitive manner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
232
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(243 citation statements)
references
References 58 publications
11
232
0
Order By: Relevance
“…If this were the case, we reasoned, expression of Orai1 in cells expressing excess TRPCs might lead to increases in SOCE, as seen in Fura2 imaging experiments. ¶ We indeed found that Orai1 increased SOCE in cells stably expressing TRPC3 or TRPC6 but not in untransformed HEK293 cells or HEK cells that were expressing unrelated molecules, such as the V2 or the V1a vasopressin receptors (8). In these studies we also showed that expression of SOCE-enhancing levels of Orai1 tends to ''silence'' ʈ spontaneous activity of TRPC3 in cells that stably overexpress these channels.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…If this were the case, we reasoned, expression of Orai1 in cells expressing excess TRPCs might lead to increases in SOCE, as seen in Fura2 imaging experiments. ¶ We indeed found that Orai1 increased SOCE in cells stably expressing TRPC3 or TRPC6 but not in untransformed HEK293 cells or HEK cells that were expressing unrelated molecules, such as the V2 or the V1a vasopressin receptors (8). In these studies we also showed that expression of SOCE-enhancing levels of Orai1 tends to ''silence'' ʈ spontaneous activity of TRPC3 in cells that stably overexpress these channels.…”
supporting
confidence: 59%
“…Expression of low levels of Orai (typically between 50 and 90 ng of Orai1-carrying pcDNA3 plasmid to transfect the cells grown to near confluence in a 60-mm dish) leads to an enhancement of SOCE between 50% and 150% for cells stably expressing either TRPC3 or TRPC6 (8). Orai1 also enhances SOCE in TRPC1-and TRPC7-expressing cells (data not shown).…”
Section: Positive and Negative Regulation Of Soce In Trpc-expressing mentioning
confidence: 93%
See 1 more Smart Citation
“…Orai1 was also shown to be associated with the complex formed by STIM1 and TRPC. Hence, the idea emerged that the function of TRPC channels might well depend on their association or not with the STIM/Orai molecules [30][31][32][33][34][35]. Our experimental evidence suggested that TRPC3 function independently from STIM/Orai and that its activity is not linked to the Ca 2+ content of the store.…”
Section: Discussionmentioning
confidence: 79%
“…Antisense From siRNA STIM1 GGCUCUGGAUACAGUGCUCtt GAGCACUGUAUCCAGAGCCtt Ambion Orai1 CGUGCACAAUCUCAACUCGtt CGAGUUGAGAUUGUGCACGtt Ambion TRPC1 CGGACUUCUAAAUAUGCUAtt UAGCAUAUUUAGAAGUCCGAAtt Oiagen TRPC3 GCAGCAGCUCUUGACGAUCUGGUAU AUACCAGAUCGUCAAGAGCUGCUGC Invitrogen TRPC4 UGUCUAUGUUGGAGAUGCUCUAUUA UAAUAGAGCAUCUCCAACAUAGACA Invitrogen TRPC5 CCCAAGUCAUUUCUAUACCUUGGUA UACCAAGGUAUAGAAAUGACUUGGG Invitrogen TRPC6 CCCAAGGAAUAUUUGUUUGAGUUGU ACAACUCAAACAAAUAUUCCUUGGG Invitrogen PKC CCAGAUUUGUGGCUUAUAAtt UUAUAAGCCACAAAUCUGGtt Qiagen PKC␦ GCCGGGACACUAUAUUCCAtt UGGAAUAUAGUGUCCCGGCUtt Ambion PCR primers STIM1 TGACAGGGACTGTGCTGAAG AAGAGAGGAGGCCCAAAGAG Invitrogen Orai1 GCTCATGATCAGCACCTGCAC GGGACTCCTTGACCGAGTTG Invitrogen TRPC1 GAGGTGATGGCGCTGAAGG GCACGCCAGCAAGAAAAGC Invitrogen TRPC3 CTGGCTCTGCTTGTGTTCAATG AGTCAGTAACTGTGATATTGGATATTG Invitrogen TRPC4 TCAGCACATCGACAGGTCAGAC CCACGGTAATATCATCCACTCGAC Invitrogen TRPC5 CTCTGATTGCGGAAGCCTCT GCAACGAACTTAAAATGTTGGATATTG Invitrogen TRPC6 AAGTATAAGGAGCTCAGAAATTTCCAT TCTGATATTGTCTTGGAGGATTATTGA Invitrogen GusB CCACCAGGGACCATCCAAT AGTCAAAATATGTGTTCTGGACAAAGTAA Invitrogen TBP GCCCGAAACGCCGAATATA CGTGGCTCTCTTATCCTCATGA Invitrogen GAPDH GCACAAGAGGAAGAGAGAGACC AGGGGAGATTCAGTGTGGTG Invitrogen EE-EF1 AGCAAAAATGACCCACCAATG GGCCTGGATGGTTCAGGATA Invitrogen reported that Orai1 and TRPC proteins form complexes together with STIM1 that participate to Ca 2+ entry [30][31][32][33][34][35].…”
Section: Sensementioning
confidence: 99%